Hydatid disease of the heart: Report of five cases and review of the literature. Issue 4 (July 1974) - Calamai, G.; Perna, A. M.; Venturini, A.
Abstract : Calamai, G., Perna, A. M., and Venturini, A. (1974). Thorax, 29, 451-458. Hydatid disease of the heart: report of five cases and review of the literature. The world literature on the surgical treatment of echinococcosis of the heart is reviewed. Few cases are surgically treated, although the disease has been known for a long time. Localization to the liver and lungs is the most frequent. Cardiopulmonary bypass techniques make possible surgical treatment of hydatid cyst of the heart. The present paper is concerned with five cases operated upon between 1959 and 1969, three males and two females, their ages ranging from 13 to 46 years. A preoperative diagnosis was made in each case. One case was operated upon under cardiopulmonary bypass. The need for cardiopulmonary bypass on a stand-by basis is emphasized. The localization of the hydatid cyst was in the left ventricular wall (three cases), right ventricular wall (one case), and multiple (one case). The frequency of cardiac echinococcosis ranges between 0·5% and 2% according to various authors. Diagnosis is achieved with the aid of laboratory tests, radiology, and angiography; but the presence of the disease must be suspected in all patients who come from endemic areas. Surgical therapy is mandatory. Due to the growth characteristics of the cyst itself, the danger of damaging the ventricular wall at operation is increased; thus it is essential to have cardiopulmonary bypass facilities immediately available.